Moose (Alces alces) population size and density in the Inuvik Region of the Northwest Territories, Canada - Davison, Tracy; Callaghan, Kristen (Rangifer, 2013)
Responding to community concerns, the Gwich’in Renewable Resources Board (GRRB) and the Government of the Northwest Territories Department of Environment and Natural Resources (ENR) conducted an aerial moose (Alces alces) survey in the Inuvik region of the Northwest Territories, Canada to estimate moose density and distribution. The survey was flown in March 2011 and a random stratified sample design was used. Local knowledge was incorporated in to the stratification of survey cells. Moose density in survey blocks ranged from 9.66 moose/100 km2 in the Ikhil Pipeline block to 0 in the Peel River block with a coarse overall moose density 2.24 moose/100 km2. Densities found were low but within expected range for the species in this region of North America based on past surveys.